Examining the effect of fatigue on shooting accuracy in young basketball players - Yanar, Şenol; Evci̇l, Ahmet Tunca; Mülazimoğlu, Olcay; Duvan, Ahmet (Kamla Raj Enterprises, 2017)
This research was carried out to examine the effects of fatigue, which result from high-intensity exercises on shooting accuracy in young basketball players. Thirteen male basketball players (15.08...